In vitro In vitro evaluation of torsional strength of evaluation of torsional strength of evaluation of torsional strength of orthodontic mini-implants - Matheus Melo Pithon; Rogério Lacerda dos Santos; Carla D'Agostini Derech; Carlos Nelson Elias; Antônio Carlos de Oliveira Ruellas; Lincoln Issamu Nojima (Universidade Estadual de Campinas, 2016)
Aim: The aim of this study was to assess the maximum torsional strength of orthodontic mini-implants of different diameters. Methods: Eighteen mini-implants measuring 10 mm in length were divided into three groups (n = 6). G1, G2 and G3 had miniimplants of 1.2, 1.4, and 1.6 mm in diameter, respectively. Mini-implants manufactured by SIN (Sistema de Implantes, São Paulo, SP, Brazil) were used in all groups. Results: The results showed statistically significant differences (p<0.0001) among the groups. The torsional strength was found to be higher in the mini-implants from the same manufacturer that had greater diameter (G3>G2>G11). Conclusion: Mini-implants with greater diameter should be used if increased torque is needed during orthodontic procedures.